NANOG Modulates Stemness in Human Colorectal Cancer - Zhang, Jingyu (2012)
NANOG is a stem cell transcription factor that is essential for embryonic development, reprogramming normal adult cells and malignant transformation and progression. The nearly identical retrogene NANOGP8 is expressed in multiple cancers, but generally not in normal tissues and its function is not well defined. Our postulate is that NANOGP8 directly modulates the stemness of individual human colorectal carcinoma (CRC) cells. Stemness was measured in vitro as the spherogenicity of single CRC cells in serum free medium and the size of the side population and in vivo as tumorigenicity and experimental metastatic potential in NOD/SCID mice. We found that 80% of clinical liver metastases express a NANOG with 75% of the positive metastases containing NANOGP8 transcripts. 3 to 62% of single cells within 6 CRC lines form spheroids in serum free medium in suspension. NANOGP8 is translated into protein. The relative expression of a NANOG gene increased 8–122 fold during spheroid formation, more than the increase in OCT4 or SOX2 transcripts with NANOGP8 the more prevalent family member. shRNA to NANOG not only inhibits spherogenicity but also reduces expression of OCT4 and SOX2, the size of the side population and tumor growth in vivo. Inhibition of NANOG gene expression is associated with inhibition of proliferation and decreased phosphorylation of G2-related cell cycle proteins. Overexpression of NANOGP8 rescues single cell spherogenicity when NANOG gene expression is inhibited and increases the side population in CRC. Thus, NANOGP8 can substitute for NANOG in directly promoting stemness in CRC.